Human Plasma Concentrations of Tolbutamide and Acetaminophen Extrapolated from in vivo Animal Pharmacokinetics Using in vitro Human Hepatic Clearances and Simple Physiologically Based Pharmacokinetic Modeling for Radio-labeled Microdose Clinical Studies - YAMAZAKI, Hiroshi; KUNIKANE, Eriko; CHIBA, Koji; NISHIYAMA, Sayako; MURAYAMA, Norie; IKEDA, Toshihiko; SUGIYAMA, Yuichi; SHIMIZU, Makiko (RADIOISOTOPES, 2015)
The aim of the current study was to extrapolate the pharmacokinetics of drug substances orally administered in humans from rat pharmacokinetic data using tolbutamide and acetaminophen as model compounds. Adjusted animal biomonitoring equivalents from rat studies based on reported plasma concentrations were scaled to human biomonitoring equivalents using known species allometric scaling factors. In this extrapolation, in vitro metabolic clearance data were obtained using liver preparations. Rates of tolbutamide elimination were roughly similar in rat and human liver microsome experiments, but acetaminophen elimination by rat liver microsomes and cytosolic preparations showed a tendency to be faster than those in humans. Using a simple physiologically based pharmacokinetic(PBPK) model, estimated human plasma concentrations of tolbutamide and acetaminophen were consistent with reported concentrations. Tolbutamide cleared in a roughly similar manner in humans and rats, but medical-dose levels of acetaminophen cleared(dependent on liver metabolism) more slowly from plasma in humans than it did in rats. The data presented here illustrate how pharmacokinetic data in combination with a simple PBPK model can be used to assist evaluations of the pharmacological/toxicological potential of new drug substances and for estimating human radiation exposures from radio‐labeled drugs when planning human studies.